170 Do Advanced Programming Options Make a Difference in Spinal Cord Stimulation?. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Roth, Steven G.; Haller, Jessica; Heran, Meghan; Lange, Steven; Campbell, Joannalee C.; De La Cruz, Priscilla; Pilitsis, Julie G.
Abstract: INTRODUCTION: Recent advancements in technology allow for additional modulation of spinal cord stimulation (SCS). Examples include application of algorithms for increasingly precise stimulation points and incorporation of accelerometers to automatically adjust parameters based on body position. The literature contains little evidence on the value of SCS devices with advanced programming capabilities. We present a prospective study of patients undergoing SCS and compare outcomes of those with standard devices to those with advanced capabilities. METHODS: Thirty-seven patients underwent SCS placement for standard indications. Of these patients, 19 received devices with standard capabilities and 18 received devices with advanced capabilities. Group assignment was based on trial device by outside providers. Outcomes were tracked through serial administration of the Visual Analog Scale (VAS) and analysis was performed using independent samples t tests. Prior to surgery both groups were equivalent in terms of average VAS scores. RESULTS: Reductions in average VAS scores were observed in both groups: 6.63 ± 0.37 to 5.32 ± 0.49 for the standard group and 6.69 ± 0.42 to 3.53 ± 0.69 for the advanced group (Figure 1). A significant difference between the groups was found for average VAS scores at most recent follow-up ( P = .042). Additionally, the mean reduction in VAS scores (delta VAS) was 1.32 ± 0.55 for the standard group and 3.17 ± 0.70 for the advanced group ( P = .046) (Figure 2). CONCLUSION: Our data suggest that patients receiving SCS devices with advanced programming capabilities experience greater reductions in pain levels at short-term follow-up than those receiving SCS devices with standard capabilities. We will continue to track these patients in the long-term and assess impact of these devices on quality of life, disability, and psychological status.